The Relationship Between Explicit Learning and Consciousness-Raising Tasks Within a Communicative Language Context - Farias, Priscila Fabiane; Roscioli, Deise Caldart; Toassi, Pamela; D’Ely, Raquel (BELT - Brazilian English Language Teaching Journal, 2015)
This study aims at investigating whether consciousness-raising tasks, used in a communicative learning environment of EFL, can be considered a valid instrument for eliciting explicit learning in that context. Five participants enrolled in the second level of a language course answered a cycle of tasks that intended to teach the use of comparatives. The materials used in this study consisted of a pre-task, consciousness-raising tasks, an untimed grammaticality judgment test, and a self-report questionnaire. Results showed that the instruments used in this research were of a valid nature for eliciting explicit learning. The findings also provide empirical support regarding the importance of consciousness-raising tasks to assist students’ second language learning in a communicative classroom environment. Despite being a small scale research, this study may contribute to a greater understanding of the SLA processes within a communicative context and highlight the importance of explicit knowledge learning within a meaning focused approach.